The Effect of Bots on Human Interaction in Online Communities - Safadi, Hani; Lalor, John P.; Berente, Nicholas (MIS Quarterly, 2024)
We investigate how bots influence human-to-human interaction in online communities. In doing so, we distinguish between reflexive and supervisory bots delegated by community participants and moderators, respectively. We hypothesize that reflexive bot activity will reduce direct reciprocity and increase generalized reciprocity and that supervisory bot activity will reduce preferential attachment among human participants. Through an analysis of almost 70 million posts on the discussion communities on Reddit, a popular platform for online discussions, we found support for the hypotheses.